Accelerating Access to Low Carbon Urban Mobility Solutions through Digitalization Project (ACCESS) - (:unkn) unknown (My University, 2026)
1. Background The United Nations Environment Programme (UNEP) is implementing a Global Programme for Sustainable Mobility. This Programme aims to support a transition to low and zero-emission sustainable mobility in low- and middle-income Countries (LMIC’